Pengembangan kompetensi pedagogik guru melalui praktik refleksi dan lesson study - Fahmi Surya Abdi; Muallim Muallim; Andi Nuzul Akbar (Journal of Smart Education and Learning, 2025)
Pedagogical competence is a fundamental element of teacher professionalism, particularly in efforts to improve the quality of learning in schools. In the context of 21st-century education, teachers are required to design student-centered, reflective, and adaptive learning environments oriented toward improving learning outcomes. This article aims to review various studies regarding the development of teachers' pedagogical competence through reflective practices and the implementation of lesson study. The method used is a systematic literature review, with articles sourced from Google Scholar, SINTA, DOAJ, and Garuda databases published between 2015 and 2025. The findings indicate that reflection strengthens a teacher's ability to evaluate the teaching process, while lesson study provides a collaborative space to develop effective learning strategies. The primary findings demonstrate that the integration of both not only enhances the quality of lesson planning and implementation but also has implications for increasing student learning motivation, strengthening professional collaboration culture, and fostering sustainable pedagogical innovation. This study confirms that reflection and lesson study are powerful strategies for supporting the development of teachers' pedagogical competence and need to be implemented systematically in both formal education and professional teacher development.